Pertanggungjawaban Pidana terhadap Pelaku Penyebaran Situs Judi Online: Studi Kasus Putusan Pengadilan Negeri Payakumbuh Nomor 123/Pid.Sus/2023 - Handriyan Cahya Mahmudi; Joko Widarto; I Made Kantikha (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of information and communication technology in the digital era has significantly transformed the forms and modus operandi of criminal acts, including the emergence of online gambling conducted through websites and social media platforms. This phenomenon raises legal challenges because the previous Indonesian Criminal Code (KUHP) regulated gambling only in its conventional form and was therefore unable to fully accommodate the characteristics of cyber-based gambling activities. In response, the government enacted the new Criminal Code (Law No. 1 of 2023), which will take full effect in 2026 and introduces important reforms through Articles 426 and 427. These provisions explicitly prohibit and criminalize any person who offers, facilitates, or participates in gambling enterprises, including those using electronic means. However, the application of these provisions to individuals who merely disseminate online gambling links remains debatable, particularly concerning their position within the structure of criminal liability. This study aims to examine the criminal liability of individuals who disseminate online gambling links via social media, as reflected in the District Court of Payakumbuh Decision No. 123/Pid.Sus/2023. The research relies on secondary data obtained from literature, legislation, legal documents, academic books, and electronic sources. This study employs a normative juridical approach, analyzed descriptively, logically, and systematically using a deductive method. The findings indicate that disseminating online gambling links is considered an act of providing an opportunity to gamble, thereby rendering the perpetrator criminally liable even though they are not directly involved in gambling activities. However, the imposition of equal criminal sanctions on both link promoters and principal actors does not fully reflect the principle of justice, as their roles and degrees of culpability differ substantially. This study emphasizes the importance of distinguishing the roles of actors within online gambling activities to ensure proportional sentencing and contributes to the scholarly development of applying the new Criminal Code to technology-based crimes.